IMPLEMENTASI HEDGING SYARIAH DALAM MINIMALISASI RISIKO ATAS FLUKTUASI KURS VALUTA ASING (STUDI PADA PT ASTRA AGRO LESTARI, TBK) - Istutik Istutik; Tita Irbah Rofifah (Politeknik Negeri Malang, 2017)
The study aims to determine the risk of losses from foreign exchange rates faced by PT Astra Agro Lestari Tbk., Implementing sharia forward hedging contract so that the risk of loss can be minimized. Type a descriptive quantitative research using secondary data that the financial statements and annual report of PT Astra Agro Lestari Tbk. Companies that have been the object of research is one of the companies listed in JII (Jakarta Islamic Index). Research shows that the application of forward hedging contract on net liabilities in foreign currencies PT Astra Agro Lestari Tbk in 2015 could reduce the value of a foreign exchange loss on the year. Accounts receivable balance of the contract will increase total assets, while the accounts payable balance of the contract will increase total liabilities. forward hedging contract Sharia can provide a positive influence on the company can be seen from the changes that make the financial statements for the better.